THE IMPACT OF THE FOOD CRISIS AND CLIMATE CHANGE ON THE LIVES OF LOCAL COMMUNITIES - Fitriani Fitriani; Hesty Tambajong; Ransta L Lekatompessy; Fransin A Kontu; Imelda C Laode (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
The food crisis and climate change have become two critical challenges facing the lives of local communities in various parts of the world. This research aims to analyze and understand the impact of the food crisis and climate change on local communities and how they adapt to these increasingly complex conditions. This study uses a qualitative approach by collecting data through in-depth interviews, participatory observation, and document analysis. The research sites involve several communities in areas that are exposed differently to food crises and climate change. The results of the study show that the food crisis and climate change are seriously affecting the daily lives of local people. Decreasing food availability, shifting weather patterns, and natural disasters further exacerbate their social and economic conditions. Local communities experience difficulties in meeting basic needs such as food, clean water and proper housing. In addition, climate change also has an impact on the agricultural sector which is the main source of livelihood for local communities. Traditional cropping patterns are no longer suited to unstable weather, and pest attacks and drought often destroy crop yields. This has resulted in reduced incomes and greater dependence on government assistance or humanitarian organizations. However, this study also identified several adaptation efforts made by local communities to deal with the food crisis and climate change. Some communities have changed cropping patterns and are cultivating crop varieties that are more resistant to climate change. The community is also actively developing local resources such as fish ponds and food processing to reduce dependence on imported food. In facing this challenge, inter-community cooperation and support from the government and international institutions are key in increasing food security and adaptation to climate change. Increasing access to sustainable agricultural technologies and financial assistance for local communities can strengthen competitiveness and reduce inequalities in the face of the impacts of the food crisis and climate change. In conclusion, this research highlights the importance of an in-depth understanding of the impact of the food crisis and climate change on local communities and adaptation efforts that can be made to strengthen their resilience. The increasing complexity of these challenges demands collective action from all parties involved to achieve sustainability and prosperity for local communities in the era of globalization and climate change.